(untitled) (Journal of the College of Basic Education, 2022)
The ancient world has recorded many incidents of corruption referred to and included in the literatureThe collusion that existed during the era of the pharaohs between the guards of the pharaonic tombs and the thieves whoThey were trying to steal its gold pieces and jewelry. Corruption is an evil tendency that wrestles with the values ​​of good in man, regardless of the nature of the systemsocial and political, as it does not exclude anyone, even if it is a virtuous society led by a prophet as a prophetMercy Muhammad (Yalha) when he describes his possession of money without justification, like his possession of a piece of fireHell ("A), and refuses to pray for a man who died, called Karkara, because he stole a cloak of moneyThe general public said that societies in all times and ages have known the phenomenon of corruption, and therefore it can be saidIt is a global and continuous phenomenon because it is not specific to a particular society or a specific historical stage